East African diploid and triploid bananas: a genetic complex transported from South-East Asia - (:unkn) unknown (My University, 2019)
Background and Aims Besides bananas belonging to the AAA triploid Mutika subgroup, which predominates in the Great Lakes countries, other AAA triploids as well as edible AA diploids, locally of considerable cultural weight, are cultivated in East Africa and in the nearby Indian Ocean islands as far as Madagascar. All these varieties call for the genetic identification and characterization of their interrelations on account of their regional socio-economic significance and their potential for banana breeding strategies. Methods An extensive sampling of all traditional bananas in East Africa and near Indian Ocean islands was genotyped with simple sequence repeat (SSR) markers, with particular emphasis on the diploid forms and on the bananas of the Indian Ocean islands, which remain poorly characterized. Key Results All the edible AA varieties studied here are genetically homogeneous, constituting a unique subgroup, here called Mchare', despite high phenotypic variation and adaptions to highly diverse ecological zones. At triploid level, and besides the well-known AAA Mutika subgroup, at least two other genetically related AAA subgroups specific to this region are identified. Neither of these East African AAA genotypes can be derived directly from the local AA Mchare diploids. However, it is demonstrated that the East African diploids and triploids together belong to the same genetic complex. The geographical distribution of their wild acuminata relatives allowed identification of the original area of this complex in a restricted part of island South-East Asia. The inferred origin leads to consideration of the history of banana introduction in Africa. Linked to biological features, documentation on the embedding of bananas in founding legends and myths and convincing linguistic elements were informative regarding the period and the peoples who introduced these Asian plants into Africa. The results point to the role of Austronesian-speaking peoples who col
Keywords: African Research